More-Than-Tech Communities: Alternative Imaginaries Within Hacking and Crafting. - MORA-GÁMEZ, FREDY; DAVIES, SARAH R. (International Journal of Communication (19328036), 2023)
Tech communities are groups that come together to engage with particular technologies. In describing two instances of such communities--hacker- and makerspaces in the United States, and the crafting activities of peasant movements in Colombia--we explore the ways in which their activities exceed their focus on and use of technology and find that practices of hacking and crafting are embedded in imaginaries of attentiveness and care. The use of technology is thus intertwined with the production of particular affects rather than being a goal in itself. We propose the notion of more-than-tech communities as a means of highlighting the ways in which there will, in such communities, always be more at stake than relationships and interactions with technology.